Dimensional Stability of Oil Palm Empty Fruit Bunch Fibre (OPEFB) Cement Board Over The Curing Period - MOHD PAZAI, AHMAD RUSYDI; Nik Soh, Nik Mohd Zaini (Journal of Structural Monitoring and Built Environment, 2025)
Oil palm fruit bunch fibre bunch (OPEFB) is a byproduct of palm oil manufacturing. Empty fruit bunch (EFB) can be recycled into compost, renewable energy, and nutrients, reducing waste and making industry more environmentally friendly and cost-effective. Asbestos and synthetic fibre exposures pose health risks, particularly mesothelioma, due to their carcinogenic effects. Natural fibres offer a sustainable alternative with comparable mechanical properties, fire resistance, and crashworthiness. They can be used in cement composite materials for biodegradability, design flexibility, and sustainability. The ratio of mixed cement- fibre is set at 3.5:1, aiming for targeted density of 1300 kg/m³. The total number of samples is 9 samples empty fruit bunch cement board (EFBCB) with the dimensions size of 350×350×12 mm. To enhance the material’s properties, hot water treatment being used at 100°C for a duration of 2 hours for treating the EFB fibre. The testing was conducted at intervals of 7, 14, and 28 days of curing process. The results demonstrated notable declines in dimensional stability and mechanical performance over the curing period. The analysis of the dimensional stability of OPEFB fibre cement board (EFBCB) during the curing period revealed significant changes in both physical and mechanical properties. The results demonstrated how the reduction in thickness, density, and other physical changes impacted the dimensional stability and mechanical performance of the boards.